UPAYA MENINGKATKAN DAYA INGAT SISWA DI MASA PANDEMI COVID-19 MELALUI PENERAPAN MODEL PEMBELAJARAN TAKE AND GIVE PADA SUBTEMA PERISTIWA KEBANGSAAN MASA PENJAJAHAN KELAS V SD N DONOTIRTO KASIHAN BANTUL YOGYAKARTA - Ilma Fahmia Nugraheni; Dhiniaty Gularso Gularso (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2021)
This study aims to improve students’ memory during the Covid-19 pandemic through the application of the take and give learning model in the sub-theme national events during the colonial period of the fifth grade at SD N Donotirto Kasihan Bantul Yogyakarta. This research is a classroom action research. The subjects of this research is 9 students from a total of 24 fifth grade students at SD N Donotirto in the academic year of 2020/2021 which was allowed to participate in the research based on a letter from the principal of SD N Donotirto Number : 25/SD. DNT/Kshn/X/2020 due to anticipating the spread of the Covid-19 virus by minimizing the crowd of students. The object of this research is students’ memory. Data collection techniques are carried out through observation, unstructured interviews and tests. The technique of quantitative descriptive data analysis was done by calculating the percentage and average score. The results of this research showed that in the initial condition, the students’ memory was obtained an average percentage of 26.7% with poor criteria and the results of observations of teaching activities with a percentage of 80% with good criteria. After taking action in cycle I, the improvement of students memory obtained an average result of 46.65% with sufficient criteria and the results of observations of teaching activities with an average percentage of 98% with very good criteria. This research was stopped until cycle II because it has achieved indicators of success with the average result of students’ memory as much as 81.1% with very good criteria and the results of observations of teaching activities with an average result of 100% with very good criteria. Thus it can be concluded that the use of the take and give learning model can improve students memory.